Arquiteturas de autoassociação derivadas de piridoxal e dihidrazidas: síntese e avaliações espectroscópicas e teóricas de interação com DNA - Martins, Francisco Mainardi (2019)
This work is about the synthesis of bis-azomethine ligands of Schiff type derived from pyridoxal and aliphatic dihydrazides and the subsequent synthesis of complexes of various transition metals containing such ligands. The ligands and synthesized complexes had their structures elucidated by single-crystal X-ray diffraction and were characterized by vibrational spectroscopies (Raman and infrared) and by ultravioletvisible spectroscopy. These ligands have characteristics, such as flexibility or rigidity, which allow the formation of self-assembly processes. The metal centers employed have different chemical affinities. These differences between the ligands and between the metal centers lead to the formation of self-assembly architectures with distinct structures. Eight structurally different complexes were obtained from salts of dioxidevanadium(V), cobalt(III), nickel(II) and zinc(II). The ligands and complexes synthesized had their interactions with ct-DNA evaluated by ultraviolet-visible Spectroscopy and by photoluminescence spectroscopy. The ligands and nickel(II) complexes had their interactions with DNA evaluated, also, by theoretical studies of molecular docking.